2021
DOI: 10.3390/su13168861
|View full text |Cite
|
Sign up to set email alerts
|

Willingness and Influencing Factors of Pig Farmers to Adopt Internet of Things Technology in Food Traceability

Abstract: : The Internet of Things technology (IoT) in food traceability provides new ideas to solve the problem of smart production and offers new ideas for the formation of safe and high-quality markets for meat products. However, scholars have studied the combination of blockchain and IoT technology. There is a lack of research on the combination of IoT and food traceability technology. Moreover, previous studies focused on the application of IoT traceability technology, taking farmers’ adoption willingness as an exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Technology use in livestock production systems continues to increase (Neethirajan & Kemp 2021 ). However, adoption of technology is affected by several factors; Sun et al ( 2021 ) identified performance expectancy, effort expectancy, social influence, personal innovation, and perceived risk as factors influencing pig farmers’ intention to adopt technology relating to food traceability. A survey of German citizens reported positive attitudes towards digital farming technology and increasing technology adoption rates by providing subsidies (Pfeiffer et al 2021 ), suggesting that the use of these technologies on pig farms is unlikely to trigger public concern.…”
Section: Resultsmentioning
confidence: 99%
“…Technology use in livestock production systems continues to increase (Neethirajan & Kemp 2021 ). However, adoption of technology is affected by several factors; Sun et al ( 2021 ) identified performance expectancy, effort expectancy, social influence, personal innovation, and perceived risk as factors influencing pig farmers’ intention to adopt technology relating to food traceability. A survey of German citizens reported positive attitudes towards digital farming technology and increasing technology adoption rates by providing subsidies (Pfeiffer et al 2021 ), suggesting that the use of these technologies on pig farms is unlikely to trigger public concern.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this study is to investigate the factors that influence behavior and its impact on the intention to adopt IMS. To achieve this, the study will use the UTAUT theoretical framework, which has been widely used to examine technology adoption in organizations [21]. Specifically, the study will focus on the relationships between the four main constructs of UTAUT, i.e., performance expectancy, effort expectancy, social influence, and facilitating conditions, and their relationships with behavior intention and use behavior, and how they affect behavioral intention and use behavior [22,23,24,25,26].…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have stated that consumers’ food waste habits are complicated as a result of the interplay between numerous home activities, and that influencing these behaviors is crucial [ 49 , 50 ]. The social impact theory might be one way that people learn from one another, resulting in attitude and behavior modification [ 51 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%